La poética y política de la empatía: el teatro como educación - Prentki, Tim (2022)
This article is built upon the premise that there is an urgent need to create a kinder, more cooperative world in order to address the crises which threaten to destroy it. The key component in this enterprise is empathy, and theatre can play a major role in training young people in the exercise of empathy. Recent developments in neuroscience (Bråten, 2007; Damasio, 1994; Denes, 2016; Singer Lamm, 2009; Stamenov Gallese, 2002) have demonstrated that the human brain’s capacity for empathy can be strengthened by frequent use. In addition, the discovery of so-called mirror neurons has revealed the extent to which the operation of our brains reflects the way in which theatre is also conceived. We are in a state of constant dialogue with ourselves and, due to the way mirror neurons stimulate us when we observe the actions and words of others, we respond like theatre audiences. Given this new scientific data, I propose that curricula in formal education need to be reconceived to take account of neurological understandings, resulting in the placing of drama processes/methodologies at their core.